“Is Universiti Sains Malaysia ready or mere wishful thinking” Universiti Sains Malaysia and the accelerated programme for excellence (APEX) 2008-2013. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2010)

(untitled)
On 3 September 2008 Universiti Sains Malaysia (USM) was publicly inducted into the Accelerated Programme for Excellence (APEX) by Malaysia’s Minister of Higher Education Y.B. Dato’ Seri Mohamed Khaled Nordin. The limelight immediately focused on USM, the nation’s second oldest university (established in 1969), not only from the 19 other public universities, and scores of private tertiary institutions but also politicians from all denominations and the general public concerned of the state of higher education in the country.